Factors Explaining Adaptive Performance in Indonesian Government Employees: A Theoretical Approach - Permata Sakti; Widya Parimita; Umi Widyastuti (Australasian Accounting Business and Finance Journal, 2024)
In 2021, the Indonesian government simplified the bureaucratic structure in all its offices. This paper aims to develop propositions about the antecedents of adaptive performance of government employees in Indonesia. This research uses quantitative methods, cross-sectional study data collection, and probability sampling techniques with proportionate stratified random sampling techniques, with a minimum sample size of 292. The measurement of the independent variables and dependent variables in the questionnaire uses a six-point Likert scale. The data analysis technique used in this research is Structural Equation Modeling (SEM) with AMOS 26 software. This paper elaborates on the work of some scholars to measure adaptive performance in developing propositions. This paper examined the role of work overload and employee readiness to change in adaptive performance, which is mediated by job satisfaction as a result of bureaucratic simplification. This paper proposes certain variables that can be employed as the determinants of adaptive performance, including work overload, employee readiness to work and job satisfaction. This paper fills the research gap in adaptive performance from a behavioral perspective due to the simplification of bureaucratic structures.
Keywords: Work overload; Employee readiness to change; Adaptive performance; Job satisfaction; Bureaucracy simplification